Learning to use atlatls: equipment scaling and enskilment on the Oregon Coast. (December 2019) - Losey, Robert J.; Hull, Emily
Abstract: Abstract : In the past, atlatls were used in hunting and warfare to throw projectiles. This article examines evidence for 'enskilment' in atlatl use from the Par-Tee site ( c. AD 100–800) in northern Oregon. Several whalebone atlatls from the site appear to have been crafted specifically to fit the hands of children. The authors argue that this is the result of equipment scaling—the process of adjusting the size of an object to fit the body size of the intended user. The authors suggest, therefore, that proficiency in the skills required to use the atlatl was probably acquired during childhood.